Penyuluhan Kepada Anak Sekolah Terkait Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Siswi Madrasah Ibtidaiyah Negeri (MIN) 1 Kota Bengkulu Tahun 2025 - Ade Zayu Cempaka Sari; Reny Suryanti; Rina Rina; Rolita Efriani; Ade Febryanti; Dira Irnameria; Reysa Pradifta (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Clean and Healthy Living Behavior (PHBS) is a crucial effort in preventing disease and improving quality of life. Elementary school children are vulnerable to various diseases due to a lack of awareness regarding personal hygiene and health practices. This community service activity aimed to increase the knowledge of 5th-grade students at MIN 1 Bengkulu City through PHBS education. The methods included pretests, lectures using PowerPoint and demonstrations, and posttests to assess knowledge improvement. Data analysis using the Chi-Square test showed a significant increase in knowledge (p=0.001), indicating a meaningful difference before and after education. These findings demonstrate that PHBS education effectively improves students’ understanding of maintaining cleanliness and personal health. This activity is expected to foster sustainable healthy behaviors in school and family environments